2012
DOI: 10.1097/jto.0b013e318244bdd4
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1 and BRAC1 mRNA Expression Levels in the Primary Tumor Could Predict the Effectiveness of the Second-Line Cisplatin-Based Chemotherapy in Pretreated Patients with Metastatic Non-small Cell Lung Cancer

Abstract: These results suggest that the ERCC1 and BRCA1 mRNA expression levels in the primary tumor at the time of diagnosis could be used for the prediction of platinum sensitivity in the treatment of NSCLC in the second-line setting. Cross-validation studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 44 publications
1
49
2
1
Order By: Relevance
“…Of the 13 included studies, 4 were for non-small-cell lung cancer, 3 were for breast cancer, and 2 were for ovarian cancer; the remaining four were for malignant pleural mesothelioma, esophageal squamous cell carcinoma, small cell lung cancer and gastric cancer. Of the 13 studies, 7 were from an EastAsian population (14,(16)(17)(18)(19)(20)24), the other 6 studies were from a European population (5,7,15,(21)(22)(23). Characteristics of included studies are summarized in Table S1.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 13 included studies, 4 were for non-small-cell lung cancer, 3 were for breast cancer, and 2 were for ovarian cancer; the remaining four were for malignant pleural mesothelioma, esophageal squamous cell carcinoma, small cell lung cancer and gastric cancer. Of the 13 studies, 7 were from an EastAsian population (14,(16)(17)(18)(19)(20)24), the other 6 studies were from a European population (5,7,15,(21)(22)(23). Characteristics of included studies are summarized in Table S1.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Figure 1 summarizes the flow chart. Among these studies, the object response rate (ORR) was provided in 9 studies (5,7,(14)(15)(16)(17)(18)(19)(20), the remaining 4 studies provided only OS or PFS (21)(22)(23)(24). Characteristics of all involved studies are summarized in Table S1.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Rate-limiting role in the nucleotide excision repair pathway that recognises and removes cisplatin DNA adducts Alterations in ERCC1 expression levels ERCC1 mRNA levels predict sensitivity to cisplatin [86,87] Hazard ratio: 0.6 [87] Low expression Increased sensitivity to PARP inhibitors [88] rs3212986 A Significantly associated with increased risk of death from NSCLC [ …”
Section: Arg 194 Trpmentioning
confidence: 99%
“…With the development of pharmacogenomics and pharmacogenetics, tumor heterogeneity is considered to be a significant factor that is responsible for the failure of conventional chemotherapeutics (6,7). In predictive biomarker studies, a number of genes have been reported to predict response to chemotherapy for solid tumors, including excision repair cross-complementation group 1 (ERCC1), breast cancer type 1 gene (BRCA1) or ADP ribosylation factor like GTPase 6 interacting protein 5 (JWA) for cisplatin (8), BRCA1, tubulin β-3 class III (TUBB3) or F-box and WD repeat domain containing 7 (FBW7) for docetaxel (9)(10)(11), thymidylate synthetase (TS) for fluorouracil (12), and ribonucleotide reductase catalytic subunit M1 (RRM1) for gemcitabine (13), murine double minute 2 (MDM2) for etoposide (14) and DNA topoisomerase 1 (TOP1) for irinotecan (15). Additionally, a few of the genes, including BRCA1, JWA and TS, have been validated for their clinical value in esophageal cancer (8,12).…”
Section: Introductionmentioning
confidence: 99%
“…In predictive biomarker studies, a number of genes have been reported to predict response to chemotherapy for solid tumors, including excision repair cross-complementation group 1 (ERCC1), breast cancer type 1 gene (BRCA1) or ADP ribosylation factor like GTPase 6 interacting protein 5 (JWA) for cisplatin (8), BRCA1, tubulin β-3 class III (TUBB3) or F-box and WD repeat domain containing 7 (FBW7) for docetaxel (9)(10)(11), thymidylate synthetase (TS) for fluorouracil (12), and ribonucleotide reductase catalytic subunit M1 (RRM1) for gemcitabine (13), murine double minute 2 (MDM2) for etoposide (14) and DNA topoisomerase 1 (TOP1) for irinotecan (15). Additionally, a few of the genes, including BRCA1, JWA and TS, have been validated for their clinical value in esophageal cancer (8,12). However, the clinical value of the aforementioned biomarkers for chemotherapeutic agents such as irinotecan (16), gemcitabine (5) and etoposide (17), which are not commonly used but exhibit moderate activity for treating esophageal cancer, remains unclear.…”
Section: Introductionmentioning
confidence: 99%